PENGEMBANGAN HANDOUT BERGAMBAR DISERTAI PETA KONSEP PADA MATERI KLASIFIKASI MAKHLUK HIDUP UNTUK SISWA SMP/MTs - Gusdianti, Wiwit; Mulyati, Mulyati; Fitriani, Vivi (STKIP PGRI Sumbar, 2014)
In teaching and learning process requires a learning media to achieve the learning objectives. The forms of learning media that are used was teaching materials. In MTsN Talaok Bayang district , the teachers Only use photocopied of worksheet, , therefore the writer wants to develope it in handout.Irregular writen are made consistent by using thesame font and size, colorful pictures that are suitable with its original, then its position is irregular and completed with pages and evaluation thats is matched to learning objektives. The aims of this research is to know the validity and practicalities of illustrated hndout with concept maps. This research is the development of the use of 4-D. The subject of this research consist of 5 validators on the validity of the texts, meanwhile on the practicalities test consists of 2 teacher and 20 student. The result of validity test ilustrated handout with concept by validator shows that illustrated handout on the valid criteria is 82,69%. The result of practicalities test is 87,24% in a very practical criteria. Based on the research that has been done, it can be concluded that illustrted with concept map in classification of creatures material that produced meets the valid and practical.